Intertextuality in media texts of genre of interview with politicians. Article 2 - Shulinova , Larysa (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article continues the research of interviews with Ukrainian politicians from the point of view of the presence of precedent intertexts and their functions. Intertextuality is one of the means of influencing on the recipient, prompting him actively to perceive the text and decode it. The following groups of precedent phenomena are analyzed: precedent names and precedent statements. It has been determined that precedent names are available in replicas of both communicants and are related to relevant precedent situations, texts and quotations. Among them are well-known for the national memory of history, culture: Taras Shevchenko, Mykhailo Hrushevsky; the names of the world-famous politicians, philosophers and religious figures: Mahatma Gandi, O. Solzhenitsyn, Donald Trump, the Holy Bartholomew etc.; the names of Ukrainian politicians, businessmen and political parties, blocs, associations as means of intertextuality can be precedent in the interview texts for all recipients, for certain politicians (one-party or political opponents), for specific situations, a certain period of political history of the country, etc. The author identifies following groups of precedent statements: quotations (direct and indirect), folklorisms (phraseological phrases, anecdotes etc.), book phraseologisms, language clichés and stamps. It has been found that intertext can become an effective mean of realizing of strategic aim – through the implementation of the illocutionary function, that is, refutation / clarification / change / confirmation of primary knowledge, experience and views of the recipient.